Composition And Biodiversity Of Insect Species In Wheat Cultivation In Gayo Highland - Muhammad Sayuthi; Husni Husni; Lukman Hakim; Hasnah Hasnah; Alfian Rusdy; Tjut Chamzurni; Firdaus Firdaus (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
The need for wheat in Indonesia continues to increase and reaches 3.9 million tons per year. Around 80% of this requirement are supplied from, Canada, Australia and the United States. Gayo highland that belongs to the territory of Aceh province is potential for wheat plantation in Indonesia. Wheat plantation, however, faces various problems, one of them is pest attack. Various insect species come to wheat plantation and are predicted to get food sources both from vegetative and generative stages. The objectives of this study were to investigate composition and diversity of insect species in wheat plant either in vegetative or generative stages by adopting survey method. The results showed that total insects found in wheat plants were 2,858 individuals covering 13 ordos. Occurrence and diversity of the insects, either in vegetative and generative stages, tend to similar.